“Sitting with myself by myself”: Indian Students in Canada During the Pandemic - Varughese, Anil; Schwartz, Saul; Sheen, Nisha (Comparative and International Education / Éducation comparée et internationale, 2022)
The number of international students from India in Canada has increased rapidly in the last 5 years. Students from India now comprise 35% of Canada’s international students and 62% of all Ontario college students. This article begins by describing the context in which the recent growth in the number of Indian international students in Canada has occurred. Then, drawing from an online national survey and qualitative interviews, it examines the major challenges experienced by Indian international students in Canada during COVID-19. Key findings include heightened, and often intersecting, psychosocial, academic, and financial disruptions experienced by Indian international students. Based on the findings, we hypothesize that the intensity of challenges faced by Indian international students is correlated with the recent commercialization of the “study-work-immigrate” pathway offered by Canada.